Applications of additive manufacturing in dentistry: A review. Issue 5 (24th July 2017) - Bhargav, Aishwarya; Sanjairaj, Vijayavenkatraman; Rosa, Vinicius; Feng, Lu Wen; Fuh YH, Jerry
Abstract: Additive manufacturing (AM) or 3D printing has been hailed as the third industrial revolution as it has caused a paradigm shift in the way objects have been manufactured. Conventionally, converting a raw material to a fully finished and assembled, usable product comprises several steps which can be eliminated by using this process as functional products can be created directly from the raw material at a fraction of the time originally consumed. Thus, AM has found applications in several sectors including automotive, aerospace, printed electronics, and healthcare. AM is increasingly being used in the healthcare sector, given its potential to fabricate patient‐specific customized implants with required accuracy and precision. Implantable heart valves, rib cages, and bones are some of the examples where AM technologies are used. A vast variety of materials including ceramics, metals, polymers, and composites have been processed to fabricate intricate implants using 3D printing. The applications of AM in dentistry include maxillofacial implants, dentures, and other prosthetic aids. It may also be used in surgical training and planning, as anatomical models can be created at ease using AM. This article gives an overview of the AM process and reviews in detail the applications of 3D printing in dentistry. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2058–2064, 2018.